Functional Outcome Following Synthetic Vertebral Body Implantation in the Management of Spinal Disorders - Faraj , Moneer K.; Â Arkawazi, Bassam Mahmood Flamerz; Abbas, Hazim Moojid; Al-Attar, Zaid (Open Access Macedonian Journal of Medical Sciences, 2020)
OBJECTIVE: Synthetic vertebral body replacement has been widely used recently to treat different spinal conditions affecting the anterior column. They arrange from trauma, infections, and even tumor conditions. In this study, we assess the functional outcome of this modality in different spinal conditions. PATIENTS AND METHODS: Thirty-six cases operated from October 2010 to December 2017. Twelve patients had spinal type A3 fractures, 11 cases with spinal tuberculosis (TB), and 13 cases with spinal tumors. They were followed clinically for a mean period of 2.4 years. RESULTS: All the cases were approached anteriorly. Seven cases had a post-operative infection. No neurological worsening reported. We had dramatic neurological improvement in all spinal TB cases. Mortality recorded in only 4 cases with metastatic spinal tumor during the mean period of follow-up. Karnofsky performance status scale showed statistically significant change for spinal TB, and tumor cases during the follow-up period, but there was no significant change in cases of spinal type A3 fractures. CONCLUSION: The positive outcome of this surgery makes it recommended for properly selected patients, especially with spinal TB and tumors.